CPEC: Investments other than China - Nawaz Ahmad; Nimra Sharif (International Journal of Experiential Learning & Case Studies, 2016)
This case study explores and engages the strategic importance of china Pakistaneconomic corridor having based on $46 billion investment. The project is expected to bring about flood of opportunities not only for the two main players but other nations which are found to be interested in making investment. The benefits seem to be game changer and expected to raise exports of Pakistan by 10% and $16 billion between china and Pakistan.in addition to this Pakistan’s major in-dustries are expected to flourish and gain an edge like that of developed nations.